2015
DOI: 10.1098/rsta.2014.0419
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric and oceanic impacts of Antarctic glaciation across the Eocene–Oligocene transition

Abstract: The glaciation of Antarctica at the Eocene-Oligocene transition (approx. 34 million years ago) was a major shift in the Earth's climate system, but the mechanisms that caused the glaciation, and its effects, remain highly debated. A number of recent studies have used coupled atmosphere-ocean climate models to assess the climatic effects of Antarctic glacial inception, with often contrasting results. Here, using the HadCM3L model, we show that the global atmosphere and ocean response to growth of the Antarctic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(77 citation statements)
references
References 54 publications
(118 reference statements)
9
63
0
Order By: Relevance
“…As such, HadCM3BL has been used exten-sively for our pre-Quaternary climate modelling work (e.g. Marzocchi et al, 2015b;Bradshaw et al, 2015;Kennedy et al, 2015;Loptson et al, 2014).…”
Section: Hadcm3blmentioning
confidence: 99%
“…As such, HadCM3BL has been used exten-sively for our pre-Quaternary climate modelling work (e.g. Marzocchi et al, 2015b;Bradshaw et al, 2015;Kennedy et al, 2015;Loptson et al, 2014).…”
Section: Hadcm3blmentioning
confidence: 99%
“…5 Some recent climate model studies have used reconstructions of late Eocene and early Oligocene topography for their control runs (Kennedy et al, 2015;Ladant et al, 2014;Lefebvre et al, 2012;Lunt et al, 2016;Zhang et al, 2010). Kennedy et al (2015) found that when an ice sheet is placed over Antarctica, the Pacific sector of the Southern Ocean surface warms significantly when the Tasman 10 Seaway is constricted as in the late Eocene, whereas when the Tasman Seaway is wider as in the early Oligocene, there is instead a weak cooling. These results contrast with Goldner et al (2014), who found a strong cooling of the Southern Ocean in response to Antarctic glaciation, albeit with an early Eocene paleogeography.…”
Section: Hypotheses 15mentioning
confidence: 99%
“…Most recent modelling studies focussed on reconstructing either early Eocene extreme (Huber and Caballero,65 2011; Lunt et al, 2012;Herold et al, 2014) or the latest Eocene -early Oligocene (Hill et al, 2013;Ladant et al, 2014;Kennedy et al, 2015) conditions. Both proxies and especially model results are relatively scarce for the middle-late Eocene considered here (Bartonian and Priabonian ∼41.2-…”
Section: Introductionmentioning
confidence: 99%